Regulasi diri kesehatan dan welas diri sebagai prediktor perilaku pencegahan COVID-19 pada sampel Indonesia - Dicky Sugianto; Jessica Amelia Anna; Sandra Handayani Sutanto (Konsorsium Psikologi Ilmiah Nusantara, 2022)
The negligence of health protocols of COVID-19 prevention in Indonesia arises concerns in the mitigation of the pandemic. This study aims to examine health self-regulation and self-compassion as predictors of COVID-19 preventive behavior. A sample consisting of 366 participants in Indonesia recruited through non-probability sampling completed an online survey. Findings showed that health self-regulation and self-compassion predict COVID-19 preventive behavior. Age is also positively correlated with COVID-19 preventive behavior. The results indicate the importance of health self-regulation and self-compassion promotion to flatten the pandemic curve.